2021
DOI: 10.1093/mnras/stab2747
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spectral study of PKS B1222 + 216 flares in 2014

Abstract: We report on a temporal and spectral study of a flat-spectrum radio quasar, PKS B1222 + 216, in a flare state to get insight into the acceleration and emission mechanisms inside the jet. It is one of the brightest and highly active blazars in the MeV–GeV regime. The long-term multiwaveband light curves of this object showed flaring activity in 2014, with two distinct flares. The work presented here includes the study of flux-index variation, flare fitting, and hardness ratio, and the spectral modelling of X-ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…The observed results points to a scenario where the blazar output is dominated by the inverse Compton scattering of the external radiation, and the jet dissipation occurs at a distance of a few hundreds of Schwarzschild radius from the central black hole, as supported by the canonical jet model (Ghisellini & Tavecchio 2009;Sikora et al 2009). Our result suggests that the γ-ray emitting region lies in the BLR/torus regions in the FSRQ PKS 1222+216, in agreement with former studies on the source during its active and quiescent states (e.g., Tavecchio et al 2011;Ackermann et al 2014;Chatterjee et al 2021). This is also consistent with some recent studies of other FSRQs (e.g., Paliya 2015;Shukla & Mannheim 2020).…”
Section: Summary and Discussionsupporting
confidence: 90%
“…The observed results points to a scenario where the blazar output is dominated by the inverse Compton scattering of the external radiation, and the jet dissipation occurs at a distance of a few hundreds of Schwarzschild radius from the central black hole, as supported by the canonical jet model (Ghisellini & Tavecchio 2009;Sikora et al 2009). Our result suggests that the γ-ray emitting region lies in the BLR/torus regions in the FSRQ PKS 1222+216, in agreement with former studies on the source during its active and quiescent states (e.g., Tavecchio et al 2011;Ackermann et al 2014;Chatterjee et al 2021). This is also consistent with some recent studies of other FSRQs (e.g., Paliya 2015;Shukla & Mannheim 2020).…”
Section: Summary and Discussionsupporting
confidence: 90%
“…Such highly energized electrons are responsible for the observed abrupt rise seen in the multi-wavelength light curves for both cases. A similar remarkable rise in the X-ray light curve has previously been seen in FSRQ PKS 1222+216 (Chatterjee et al 2021). Very short lived X-ray flares have also been observed in PKS 2005−489 (Zhu et al 2018), where the variability timescale is found to be <30 s. Furthermore, Markowitz et al (2022) also found modest X-ray flares in Mkn 421 that last for less than a day.…”
Section: Implications Of Shocks On the Emission Signaturessupporting
confidence: 69%